0208 Invited keynote: obstacles to conducting occupational epidemiological research in developing countries. (21st August 2017) - Aw, Tar-Ching
Abstract : The reasons advocated for conducting epidemiological studies in developing countries often include a need to improve the data base for prevention of ill health, including occupational diseases. Evidence based on research in developed countries may not be wholly relevant to developing countries because of differences in the environment, culture, health behaviour, health systems, and other factors. The obstacles to conducting occupational epidemiology studies in developing countries include: a) A lack of understanding of the purpose and nature of epidemiological studies. This often leads to potential study populations declining to participate. b) Difficulty in defining homogenous study populations. This is especially true in developing countries with diverse mutinational expatriate workers. c) The absence of an infrastructure and support for conducting epidemiologcal research. Ethical committees meet infrequently. Statistical advice is difficult to obtain. Laboratories for analysis of environmental and/or biological samples are often not readily available. d) Logistical difficulties include difficulty in contacting and recruiting study participants. Organising teams of interviewers and research assitants can also be problematic. e) The nature of the research. A questionnaire may well have to be translated into several languages. There may be a reluctance by study participants to provide biological samples such as a venous blood sample. If environmental monitoring devices are to be placed in workplaces, this can be viewed with apprehension. Despite these obstacles there are approaches to overcoming the hurdles identified, and increasing occupational epidemiology research in developing countries.